S104 Double-blind Multi-centre Randomised Controlled Trial Of Vitamin D3 Supplementation In Copd (vidico). (10th November 2014) - Martineau, AR; James, WY; Hooper, RL; Barnes, NC; Jolliffe, DA; Bhowmik, A; Rajakulasingam, RK; Choudhury, AB; Simcock, DE; Corrigan, CJ; Hawrylowicz, CM; Griffiths, CJ
Abstract : Introduction and objectives: Inadequate vitamin D status is common in patients with COPD, and it associates with susceptibility to upper respiratory infection (URI) – a major precipitant of exacerbation. Multi-centre trials of vitamin D supplementation for prevention of exacerbation and URI in COPD are lacking. We therefore conducted a multi-centre double-blind randomised placebo-controlled trial of vitamin D supplementation for the prevention of moderate/severe exacerbation and URI in adults with COPD. Methods: Two hundred and forty patients were allocated to receive a 2-monthly oral dose of 3 mg vitamin D3 or placebo for one year. Co-primary outcomes were time to first moderate/severe exacerbation and time to first URI. Secondary outcomes included peak severity and area under the curve for exacerbation symptoms. A pre-specified sub-group analysis was conducted to determine whether effects of the intervention on co-primary outcomes were modified by baseline vitamin D status. This trial is registered with ClinicalTrials.gov (NCT00977873 ). Results: 122 participants were allocated to the intervention arm of the trial, and 118 to the control arm. Vitamin D supplementation did not influence time to first exacerbation (HR 0.86, 95% CI 0.60–1.24, p = 0.42) or time to first URI (HR 0.95, 95% CI 0.69–1.31, p = 0.75) in the study population as a whole, but it did reduce peak severity (p = 0.042) and area under the curve (p = 0.032) for exacerbation symptoms. Pre-specified sub-group analysis revealed that vitamin D supplementation was protective against moderate/severe exacerbation among the 148 participants with baseline serum 25-hydroxyvitamin D (25[OH]D) concentration < 50 nmol/L (aHR 0.57, 95% CI 0.35 to 0.92, p = 0.021), but not among the 92 participants with baseline serum 25(OH)D ≥ 50 nmol/L (aHR 1.45, 95% CI 0.81 to 2.62, p = 0.21; P for interaction = 0.021). Baseline vitamin D status did not modify the effect of vitamin D supplementation on risk of URI (P for interaction = 0.41). Conclusions: Vitamin D supplementation protected against moderate/severe exacerbation, but not upper respiratory infection, in COPD patients with baseline 25(OH)D < 50 nmol/L. It also modestly reduced peak severity and area under the curve for exacerbation symptom scores, irrespective of baseline vitamin D status.